1998
DOI: 10.1111/j.1432-2277.1998.tb01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate and long-term results after pediatric heart transplantation: incidence and role of pretransplant diagnosis

Abstract: From November 1985 to 31 July 1997, 65 pediatric patients underwent heart transplantation at Bambino Gesù Hospital in Rome. Two of them underwent retransplantation, both 6 years after the first transplant. The 67 transplant patients had a mean age of 59 months; 11 were under 1 year of age. Their indications for transplantation were cardiomyopathies (38), lymphocytic myocarditis (8), and congenital heart diseases (19). Two patients of the first group successfully received a combined heart and kidney transplant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This study shows that good survival figures are achievable without the use of long‐term steroids. Actuarial survival compares favourably with data from the Registry of the International Society of Heart and Lung Transplantation (1, 2) and other centres where steroids are used in some (5–8, 14, 15) or all (10) children and results at 1, 5 and 10 yr range from 58–80%, 60–70% and 42–66%, respectively. Other authors also have demonstrated excellent actuarial survival of 80, 76 and 76% at 1, 5 and 10 yr (16) and 79 and 69% at 1 and 5 yr (17) using a steroid‐free regimen.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This study shows that good survival figures are achievable without the use of long‐term steroids. Actuarial survival compares favourably with data from the Registry of the International Society of Heart and Lung Transplantation (1, 2) and other centres where steroids are used in some (5–8, 14, 15) or all (10) children and results at 1, 5 and 10 yr range from 58–80%, 60–70% and 42–66%, respectively. Other authors also have demonstrated excellent actuarial survival of 80, 76 and 76% at 1, 5 and 10 yr (16) and 79 and 69% at 1 and 5 yr (17) using a steroid‐free regimen.…”
Section: Discussionmentioning
confidence: 74%
“…The larger multi‐centre reports give an excellent overall picture of contemporary pediatric heart transplantation (1–4) but do not allow comparison between the different management regimens, which vary between centres. Many centres use an immunosuppressive maintenance regimen including steroids for some (5–9) or all (10) of the children.…”
mentioning
confidence: 99%